Parental Perceptions of the Teaching Profession: Factors That Predict Parental Encouragement of Students to Enter the Teaching Profession - Steven Christensen; Randall S Davies; Ross A. A. Larsen; Scott Harris; Joseph Hanks; Bryan Bowles (MDPI AG, 2022)
This study examines factors that influence parent's willingness to encourage their children to consider teaching as a career. Using structural equation modeling, we identified four factors that are highly predictive of a parent's willingness to encourage their children to consider teaching and their belief that teaching would be their best career option. Results indicated that parents were more likely to encourage their children to become teachers when people outside the family had encouraged the children to teach, if the parents believed their child would be a good teacher, and if parents thought that expectations placed on teachers were reasonable. Results also showed, however, that when considering other professions, parents were much less likely to encourage their children to become teachers in favor of other professions.